Ultrasonic evaluation of thick concrete with one accessible side only - Chua, Antonio B. Jr
This study aimed to investigate the applicability and viability of the ultrasonic indirect transmission method for the evaluation of thick concrete. The indirect transmission method is most commonly used for defect detection and quality control. A void was fabricated in five specimens with increasing thickness and increasing void depth from the testing surface. The void depth and location was determined through indirect transmission method and was compared to the actual void depth, the errors were ranging from 3-54% as the thickness of both the specimen and the void depth increases. The 28th day compressive strength of the specimens was determined using the Proceq conversion curve equation which has an R² value of 0.6950 generated from the compressive strength and ultrasonic pulse velocity of the concrete cylinders prepared for each specimen. Another method used for the compressive strength determination is the attenuation parameter of the thick concrete specimens. Relating attenuation with the ultrasonic pulse velocity, the 28th day compressive strength was also determined using this method. Larger errors were observed ranging from 11-34% from the actual compressive strength compared to the Proceq conversion curve equation which yielded less error ranging from 1630-18.03% in the strength estimation. The dynamic modulus of elasticity was also obtained by an equation which relates the Poisson's Ratio, density, and ultrasonic pulse velocity of the concrete. The obtained values of the dynamic modulus of elasticity have error ranging from 0.10-7.90% of the values obtained through direct transmission method which was the basis for validation. The static modulus of elasticity was obtained by equations from journals which converts the dynamic to static modulus of elasticity.